Unsustainable glacier ablation at 78 N latitude, Linne’breen, Svalbard - Schiff, Caleb (2009)
Caleb's project was to compare the glacier margin positions documented by aerial photographs and to place the observed glacier retreat in the context of measure changes in mass balance.